Studies on the Nutritional Requirement of Vibrio Comma - SAITO, Keiko (Journal of the Japanese Association for Infectious Diseases, 1960)
The nutritional requirement, especially the salt demand of Vibrio comma was studied in view of the similarity of Pseudomonas enteritis, the halophilic pathogenic bacteria discovered by I. Takikawa 1955. Several kinds of salt, sodium, potassium, magnesium and ammonium salt were used for the test. Vibrio comma grew best in the peptone medium with NaCl, the optimum concentration being 0.3 Mol and that of other kinds of salt ranging from 0.075 to 0.3 Mol. Salts of polyvalent base, for instance Na2SO4 demonstrated a lower optimum concentration as compared with salts of monovalent base (Table 2. Fig. 2-5) In the peptone medium containing glucose but no salt a better growth of Vibria comma could not be observed, but small amounts of NaCl added in it promoted the growth better than salt alone in the peptone medium. Optimum concentration of glucose was higher than that of dissociatable salts. (Table 3. Fig. 6) The good effect of the salts and glucose on the growth of Vibrio comma was considered to be due to the osmotic pressure of the medium and perticularly thespecial agency of the salt ions. The optimum acidity of medium to the grouth of Vibrio comma was neutral, contrary to the common opinion. This opinion way be attributable to the good effect of salts, especially the metal ions added to alkalize the medium and to the overlooking of pH alteration. (Table 4. Fig. 7) When other conditions, i. e. salt and glucose concentration were adequate, peptone or other special nutritious were required only in a small amount. (Table 5, 6. Fig. 8, 9) According to these data Vibrio comma demonstrates a halophilic nature characteristic of the bacteria of marine sourse, Pseudomonas enteritis Takikawa. It was assumed that Vibrio comma was of marine source like Pseudomonas enteritis, but its divergence from the marine environment went further back than the latter, so that Vibrio comma was more accustomed to the land environment.